2022
DOI: 10.3389/fpls.2021.755830
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variations in Seed Set and Pollen Limitation in Populations of the Rare Generalist Species Polemonium caeruleum in Poland

Abstract: A vast majority of angiosperms are pollinated by animals, and a decline in the number and diversity of insects often affects plant reproduction through pollen limitation. This phenomenon may be particularly severe in rare plant species, whose populations are shrinking. Here, we examined the variability in factors shaping reproductive success and pollen limitation in red-listed Polemonium caeruleum L. During a 5-year study in several populations of P. caeruleum (7–15, depending on year), we assessed the degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…Variation in pollen limitation within species is not unusual (Burd, 1994; Ashman et al, 2004; Burd et al, 2009), and can vary across years and populations, depending on environmental factors, presence of co‐flowering species, fluctuations in pollinator abundance, plant population size, and other factors (Knight et al, 2005). For example, significant interannual variation in pollen limitation was observed in the rare plant Polemonium caeruleum L. (Polemoniaceae), possibly in part due to variation in pollinator visitation frequency and temperature (Ryniewicz et al, 2021). Our results compared to prior studies suggest that there is also interannual or geographic variation in pollen limitation in D. muscipula .…”
Section: Discussionmentioning
confidence: 99%
“…Variation in pollen limitation within species is not unusual (Burd, 1994; Ashman et al, 2004; Burd et al, 2009), and can vary across years and populations, depending on environmental factors, presence of co‐flowering species, fluctuations in pollinator abundance, plant population size, and other factors (Knight et al, 2005). For example, significant interannual variation in pollen limitation was observed in the rare plant Polemonium caeruleum L. (Polemoniaceae), possibly in part due to variation in pollinator visitation frequency and temperature (Ryniewicz et al, 2021). Our results compared to prior studies suggest that there is also interannual or geographic variation in pollen limitation in D. muscipula .…”
Section: Discussionmentioning
confidence: 99%
“…The fertility of flowers that were exposed to supplementary insects was compared with that under natural open pollination. Pollen limitation (PL) was calculated as PL = (P s -P o )/P Max , where P s is the yield or fruit weight after supplementary pollination, P o is the yield or fruit weight from the control treatment (open pollination) and P Max is the larger of the two values (Baskin & Baskin, 2018;Ryniewicz et al, 2022). Twosided t-tests were used determine if PL was significantly (P < 0.05) lower or higher than zero.…”
Section: Pollen Limitationmentioning
confidence: 99%
“…Pollen limitation (PL) was calculated as PL = (P s -P o )/P Max , where P s is the number of seeds, etc. from the supplementary pollination treatment, P o is the number of seeds from the control treatment (open pollination) and P Max is the larger of the two values (Baskin & Baskin, 2018;Ryniewicz et al, 2022). Data are from the various authors shown in Table S5.…”
Section: Relationship Between Fertility and The Pollinator Communitymentioning
confidence: 99%
“…Pollinator-mediated selection of flower traits is one of the main evolutionary mechanisms shaping plant-pollinator interactions [13,16,63,64]. The spatial variation of the relationships between both groups of organisms translates into differentiation of the reproductive success of plants [5,8,19,61,65].…”
Section: Introductionmentioning
confidence: 99%